Protein import into yeast mitochondria: the inner membrane import site protein ISP45 is the MPI1 gene product. - Horst, M (1993)
Protein import across both mitochondrial membranes is mediated by the cooperation of two distinct protein transport systems, one in the outer and the other in the inner membrane. Previously we described a 45 kDa yeast mitochondrial inner membrane protein (ISP45) that can be cross-linked to a partially translocated precursor protein (Scherer et al., 1992). We have now purified ISP45 to homogeneity and identified it as the product of the nuclear MPI1 gene. Identity of ISP45 with the MPI1 gene product was shown by microsequencing of three tryptic ISP45 peptides and by demonstrating that an antibody against an Mpi1p-beta-galactosidase fusion protein specifically recognizes ISP45. Antibodies monospecific for ISP45 inhibited protein import into right-side-out mitochondrial inner membrane vesicles, but not into intact mitochondria. On solubilizing mitochondria, ISP45 was rapidly converted to a 40 kDa proteolytic fragment unless mitochondria were first denatured with trichloroacetic acid. The combined genetic and biochemical evidence identifies ISP45/Mpi1p as a component of the protein import system of the yeast mitochondrial inner membrane.